Paralelitas Unsur-Unsur Penciptaan Manusia (Analisis Intertekstualitas Antara Al-Qur’an dan Al-Kitab) - Ekatul Hilwatis Sakinah; Syahidil Mubarik Mh (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2023)
Abstract The elements of human creation mentioned by al-Qur'an and al-Kitab have similarities, although it needs to be recognized that al-Qur'an is more explicit in explaining it. This then triggers an expansion of meaning carried out by the Qur'an against al-Kitab. This research focuses on the elements of human creation using the theory of intertextuality initiated by Julia Kristeva. There are two main problems that will be answered in the research, namely how the Qur'an and al-Kitab explain the elements of human formation and how the intertextuality approach is able to explain the elements of human formation contained in the Qur'an and al-Kitab. The purpose of this research is to find the relationship between the elements of human creation in al-Qur'an and al-Kitab. The method used in this research is descriptive analytic with library research. The data were collected through books, articles, journals, and writings related to the research theme. The results show that between al-Qur'an and al-Kitab in explaining the elements of human creation has a transposition of textual relationships that are not only included in the parallel category but also in the categories of expansion, existence, and conversion. Expansion occurs when the Qur'an has expanded the meaning of the elements of human creation in al-Kitab, namely soil, water, and spirit. Existence is when the Qur'an raises water terms explicitly as an element of human creation, including semen. Conversion is the contradiction between the texts of al-Qur’an and al-Kitab regarding who was created from soil. Al-Kitab narrates that only Adam was created from soil and Hawa was created from Adam's rib, while the Qur'an narrates that Adam and Eve were created from the same element, namely soil. Keywords: al-Qur'an, al-Kitab, Intertextuality, Human, Creation